Development of a framework to guide research into policies promoting physical activity and healthy diets in the European context: the system-based Policy Evaluation Network (PEN) framework. (29th November 2022) - Kamphuis, Carlijn B M; Forberger, Sarah; Lien, Nanna; Rehfuess, Eva; Luszczynska, Aleksandra
Abstract: Background: The Policy Evaluation Network (PEN) is a multidisciplinary Pan-European research consortium focussing on policies affecting dietary intake, physical activity and sedentary behaviour. At the start, the PEN consortium expressed the need for an overarching, system-based framework covering the complexities between the different domains of the policy process (design, implementation and outcomes) in order to execute all research activities in a coherent way. This article describes the PEN framework itself and its development process. Methods: A staged approach to the development of a system-based framework was executed between February 2019 and February 2022. We started with a point-of-departure framework, made use of existing models, collected PEN outputs at different project stages (through online meetings, e-mail exchanges and workshops with PEN researchers) and drew updated versions of the framework, which resulted in the system-based PEN framework. Results: The system-based PEN framework depicts the policy process as a complex system, visualizing the dynamic interrelations between and within policy domains (i.e. policy design, policy implementation and policy outcomes), the ways they interact with the context, and how to assure a focus on equity in each domain. Conclusions: The system-based PEN framework may guide researchers and professionals involved in the evaluation of health- or sustainability-related policies to consider their evaluation in a comprehensive picture, including domain interactions, contextual influences and equity considerations, as these can have important implications for the scope of their research. The stage-based process as applied for the development of the PEN framework can serve as a template for other research projects wishing to develop their own framework.